Formulation, characterization and in vitro evaluation of floating microspheres of famotidine as a gastro retentive dosage form - Jain, Abhishek Kumar; Jain, C P; Tanwar, Y S; Naruka, P S (Asian Journal of Pharmaceutics (AJP), 2014)
different polymers, i.e. acrycoat S100 and cellulose acetate. The size or average diameter (davg) and surface morphology of the prepared microspheres were recognized and characterized by the optical and scanning electron microscopic methods, respectively. In vitro drug release studies were performed and the drug release kinetics were evaluated using the linear regression method. Effects of the stirring rate during preparation, polymer concentration on the size of the microspheres and drug release were also observed.The prepared microspheres exhibited prolonged drug release (18 h) and remained buoyant for more than 12 h. The mean particle size increased and the drug release rate decreased at a higher polymer concentration. No significant effect of the stirring rate during preparation on drug release was observed. In vitro studies demonstrated a diffusion-controlled drug release from the microspheres. The objective of the present study was to develop floating microspheres of FM in order to achieve an extended retention in the upper gastrointestinal tract, which may result in enhanced absorption and thereby improved bioavailability. The prepared microspheres were evaluated for particle size, in vitro release and buoyancy and incorporation efficiency.The effect of various formulation variables on the size and drug release was investigated. In vitro drug release studies were performed and the drug release kinetics were evaluated using the linear regression method. FM was obtained as a gift sample from Intas Pharmaceuticals, Ahmedabad, India. Polyvinyl alcohol was obtained from S.D. Fine Chemicals Ltd., Mumbai, India. Dichloromethane, acrycoat S100, cellulose acetate and Tween 80 were obtained from Central Drug House (P) Ltd., Delhi, India. All other chemicals/reagents used were of analytical grade. A UV/visible spectrophotometer was used for drug analysis. Experimental results were expressed as mean Â± SD. Chi-square test and one-way analysis of variance (ANOVA) were applied to check significant differences in drug release from different formulations. Differences were considered to be statistically significant at P = 3.23, DF = 1, i.e. P < 0.05. The prepared floating microspheres exhibited prolonged drug release, i.e. <18 h, and the floating time was <12 h in 0.1 N HCl.The mean particle size of the prepared floating microspheres increased but the drug release rate from the microspheric-coated layer decreased as the polymer concentration increased. No significant effect of the stirring rate during preparation on drug release was observed. In vitro data obtained for floating microspheres of FM showed excellent floatability, good buoyancy and prolonged drug release. Microspheres of different size and drug content could be obtained by varying the formulation variables. Diffusion was found to be the main release mechanism.Thus, the prepared floating microspheres may prove to be potential candidates for multiple-unit delivery devices adaptable to any intragastric condition.